Agricultural Environmental Sensing Application Using Wireless Sensor Network for Automated Drip Irrigation - Manish B, Giri; Pippal, Ravi Singh (International Journal of Computer Sciences and Engineering, 2025)
The advent of Wireless Sensor Networks (WSN) has given a new directions to agriculture research and farm trading. Currently every day WSN has wide use in agriculture sector. In this paper, we have tendency to review the potential WSN application that specifies the problems and necessary requirements for drip irrigation for the optimum utilization of the available water. We have tendency to gift works that is associated to use WSN in agriculture correctness and production management. In this regard, various methods of WSN deployment and implantations are surveyed. So we tried to highlight the challenges and problems of these solutions, while identifying the factor for improving the intelligent drip irrigation system.